MENINGKATKAN PEMAHAMAN KOSAKATA BENDA ANAK TUNARUNGU MELALUI METODE MATERNAL REFLEKTIF DI KELAS D II B DI SDLBN TARANTANG LIMA PULUH KOTA - Sri - Pujiwati (Jurnal Penelitian Pendidikan Khusus, 2012)
Against the background of this research by the problems of three deaf children in the class D II B Primary School of Extraordinary Affairs Tarantang do not understand the vocabulary items. Assessments of children can read words but do not know the meaning of the a noun, when the child is asked to take one thing at the mention teachers are among the many objects on the table was the child cannot do that and take things from, as long as these efforts teachers in child learner using the lecture method, asked questions, and teacher training but the effort was not as expected. The purpose of this study is to improve the ability to understand a the vocabulary Maternal Reflective objects through method (MMR) in class D II B Extraordinary District Elementary School District Fifty Tarantang City. This type of research is action research class (classroom action research) is conducted in collaboration. The results showed that during the cycle I held six sessions in the learning process that starts from the child spoke spontaneously about the child sees a picture, then show the real objects or pictures, to say the names of objects or images with a straight face or lips form a very clear and is followed by students. Cycle II held five meetings with each cycle beginning with the planning, implementation, action, observation, and reflection.